Global Warming : Causes, Impacts and Remedies - Raj Singh, Bharat; Raj Singh, Bharat (IntechOpen, 2015)
Global warming has become perhaps the most complicated issue facing world leaders. It is becoming clear that humans have caused most of the past century's warming by releasing heat-trapping gases as we power our modern lives mainly by the burning of fossil fuels and forests. Whatever the uncertainties of climate models are, mankind has to strive very fast toward reduction in the huge amount of greenhouse gases emitted into the atmosphere in order to preserve natural resources and living organisms by introducing new advances on alternative fuels and other related technologies. This book presents the state-of-the-science fundamentals on the origin of Global Warming. The aim of the book is to create awareness among the energy engineers, academicians, researchers, industry personnel and society as a whole to help to stop the impact of climate change. In this book, chapters received from various authors are placed in three sub- sections - Causes of Global Warming, Impacts / Threats / Consequences of Global Warming and Remedies to the Global Warming.
English
Keywords: Climate change; Climate change